Transmural capillary ingrowth is essential for confluent vascular graft healing. (January 2018) - Pennel, Timothy; Bezuidenhout, Deon; Koehne, Josepha; Davies, Neil H.; Zilla, Peter
Graphical abstract: Abstract: Spontaneous endothelialization of synthetic vascular grafts may occur via three independent or concurrent modalities: transanastomotic (TA) outgrowth, transmural (TM) ingrowth or fallout (FO) from the blood. The limited TA and FO endothelialization, which occurs in humans, results in poor long-term patency in the small diameter position, where TM ingrowth may offer a clinically relevant alternative. To achieve sequential analysis of each mode of healing, loop grafts comprising anastomotically isolated angiopermissive polyurethane control grafts were abluminally sealed using either ePTFE wraps or solid polyurethane skins and implanted in the rat infrarenal aortic loop model for twelve weeks. Positive control grafts showed improved endothelialization and patency compared to the abluminally isolated mid-grafts. Furthermore, the mid-graft healing was accelerated with surface heparin and heparin-growth factor (VEGF, PDGF) modification in a three-week sub-study. We are thus able to distinguish between the three vascular graft endothelialization modes, and conclude that fallout plays a secondary role to TM healing. The increased endothelialisation for growth factor presenting grafts indicates the promise of this simple approach but further optimization is required. Statement of Significance: In addition to the full elucidation of, and differentiation between, the three healing/endothelialisation modes of vascular grafts, the significance of the work relates to the near-complete lack of endothelialisation of small diameter vascular grafts in humans (1–2 cm transanastomotic outgrowth on a graft that may be 60 cm long) even after decades of implantation. The concomitant retained midgraft thrombogenicity leads, together with anastomotic hyperplastic responses, to poor long-term outcomes. The large impact of successful translation of the current research to the achievement of full endothelialisation of long peripheral grafts in humans via transmural ingrowth (half a millimetre distance; thickness of the graft wall), is evident, and supported by the large improvements in clinical patencies achievable in by pre-seeding of ePTFE grafts with confluent endothelia.